Effect of giving young coconut water and isotonic drinks on the recovery of dehydration status after training in pencak silat athletes - Samuel, Samuel; Hizni, Alina; Santoso, Hari (JAND: Journal of Applied Nutrition and Dietetic, 2025)
This study evaluates the effectiveness of different types of post-exercise drinks on rehydration in pencak silat athletes. Prolonged exercise in hot environments leads to physiological changes due to depleted glycogen stores and fluid-electrolyte loss through sweat. The aim of this study was to analyze the average difference between the effects of young coconut water (Cocos nucifera) and commercial isotonic drinks on the rehydration process. This experimental research involved dividing subjects into two treatment groups: Group 1 received young coconut water, while Group 2 received a commercially available isotonic drink. Dehydration status was assessed through measurements of body weight, urine pH, and urine specific gravity. Paired t-tests were used to analyze within-group differences before and after treatment, while unpaired t-tests compared differences between groups. The average fluid intake for rehydration was 1062.5 ml. Fluid administration had a significant effect on dehydration status (p < 0.05). A significant increase in urine pH was observed: 1.63 for coconut water and 0.97 for isotonic drinks. These results indicate a difference in the effectiveness of coconut water and isotonic drinks on hydration recovery.